2007
DOI: 10.1002/ana.21064
|View full text |Cite
|
Sign up to set email alerts
|

Results of treatment changes in patients with apparently drug‐resistant chronic epilepsy

Abstract: This study provides a quantitative estimate of the value of changing drug therapy in patients in whom seizures were previously uncontrolled by previous therapy. The application of a systematic protocol to the treatment of chronic epilepsy will improve seizure control in a substantial proportion of cases. The rather nihilistic view that intractability is inevitable if seizure control is not obtained within a few years of the onset of therapy is incorrect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
171
5
21

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(228 citation statements)
references
References 26 publications
31
171
5
21
Order By: Relevance
“…It has been shown that about 15 % of pharmacoresistant patients become seizure-free after responding to the third, fourth, or later AED that is tried in the course of systematic treatment. This observation was independent of the AED used [39,40]. Thus, there are clearly late responders to specific AEDs, as has been also shown in phase III trials designed to license new AEDs.…”
Section: Genetic Biomarkers For Pharmacoresponsesupporting
confidence: 58%
“…It has been shown that about 15 % of pharmacoresistant patients become seizure-free after responding to the third, fourth, or later AED that is tried in the course of systematic treatment. This observation was independent of the AED used [39,40]. Thus, there are clearly late responders to specific AEDs, as has been also shown in phase III trials designed to license new AEDs.…”
Section: Genetic Biomarkers For Pharmacoresponsesupporting
confidence: 58%
“…It is true that no large‐scale study has been carried out that confirms or refutes this proposition, but with the large number of new therapies made available in recent years, and the indisputable advances in the science of epileptology, including surgery and neuroimaging, it would be surprising if the medical prognosis has not improved. Even if individual drugs result in seizure control in only a small percentage of patients, the additive effect of a number of these drugs tried in turn results in a markedly improved overall prognosis 28. Furthermore, there is plenty of anecdotal evidence that prognosis has been transformed.…”
Section: Today's Theories and Practices Which May Not Withstand The Tmentioning
confidence: 99%
“…There are of course costs well beyond monetary values. Observational studies have demonstrated that some patients who have not responded to several anti-epileptic drugs in the past, and might therefore be expected to continue to have seizures despite trials of further anti-epileptic drugs [2], might in fact occasionally respond to a new anti-epileptic drug [3,4].…”
Section: Sanjay Sisodiyamentioning
confidence: 99%